Simultaneous reduction of NOx and smoke emissions with low viscous biofuel in low heat rejection engine using selective catalytic reduction technique - Karthickeyan, V.; Thiyagarajan, S.; Geo, Varuvel Edwin; Ashok, B.; Nanthagopal, K.; Ong, Hwai Chyuan; Vignesh, R. (Elsevier, 2019)
The present work offered a comprehensive investigation on engine characteristics of single cylinder Direct Injection (DI) diesel engine fuelled with Lemon oil (LO) biofuel. LO was obtained from the peels of lemon using steam distillation process. The physio-chemical properties of LO were analysed based ASTM biodiesel standard and compared with diesel. The chemical composition of LO was observed with Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography and Mass Spectrometry (GC–MS). In-order to enhance the properties of LO, a cetane enhancer namely Pyrogallol (PY) was added. The engine combustion chamber components namely piston head, cylinder head and intake and exhaust valves were thermally coated with Partially Stabilized Zirconia (PSZ) which converted the conventional engine into low heat rejection engine. In the PSZ coated engine, enhanced performance and combustion characteristics were observed with LO and PY blend. Declined carbon monoxide (CO), hydrocarbon (HC) and smoke emissions were observed with LO and PY blend in coated engine. Further, the work was extended with the application of Selective catalytic reduction (SCR) and Catalytic Converter (CC) as post treatment system for the reduction of NOx emission. With post treatment, LO and pyrogallol in PSZ coated engine showed lower NOx emission than diesel and LO. Consequently, LO and pyrogallol in PSZ coated engine with post treatment was considered as more advantageous than other fuel samples on account of its performance, combustion and emission characteristics. © 2019 Elsevier Ltd